2020
DOI: 10.23947/2334-8496-2020-8-3-113-122
|View full text |Cite
|
Sign up to set email alerts
|

Educational Challenges of Roma Minorities: The Case of the Republic of North Macedonia

Abstract: Linguistic diversity comes in various forms. The most common ways of developing knowledge of more than one language according to some authors are either by learning a second language through participation in some form of bilingual education or being raised in a bilingual environment, such as school or a bilingual family. The phenomenon of development of literacy competencies of minority groups, specifically, the context of Roma people, in the Republic of North Macedonia, whose mother tongue is not even conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Concerning the educational level attained by both parents, it is observed that these are not significantly related to the socio-educational adaptation of their children. Similarly, the study by (Rizova et al 2020) observed that parents with little school education combine all their efforts to achieve quality education for their children because an education in which different linguistic or social origins are actively working together will be more inclusive (Zilka 2020).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Concerning the educational level attained by both parents, it is observed that these are not significantly related to the socio-educational adaptation of their children. Similarly, the study by (Rizova et al 2020) observed that parents with little school education combine all their efforts to achieve quality education for their children because an education in which different linguistic or social origins are actively working together will be more inclusive (Zilka 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Currently, schools are obliged to care for students from diverse cultural and linguistic backgrounds (Babane 2020), which combined with, in some cases, a lack of motivation (Murua-Carton et al 2012) and inadequate teacher training (Rizova et al 2020), causes inclusive education to become an increasingly utopian dream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the employee enjoys the work environment in which he/she works, the employee will feel at home in his/her workplace to do activities so that work time is used effectively and optimistic employees' work performance is also high (Alhamda et al, 2020;Alzamel et al, 2020;Chalikias et al, 2020;Gulzar et al, 2020;Liao et al, 2020;Riyadi et al, 2020). The work environment includes established working relationships between fellow employees and employment relationships between subordinates and superiors and the physical environment in which employees work (Achu Ayuk et al, 2020;Bove, 2020;Collier-Bordet et al, 2020;Rizova et al, 2020;Tsitsovits, 2020;Victoria & Ortigosa, 2020).…”
Section: Work Environmentmentioning
confidence: 99%
“…The social distance between the family and the educational institution prevents acknowledging how the system works, it reduces the value that families give to their children’s education (Clavell-Bate, 2012; Pantea, 2015) and makes fears emerge (Myers et al, 2010), mainly related to the gender roles inherited by a patriarchal society (Clavell-Bate, 2012; Pantea, 2015; Reimer, 2016). On the other hand, the parents’ level of education (Afanasieva et al, 2020; Fundación Secretariado Gitano, 2013; Laparra et al, 2011; Rizova et al, 2020) or the linguistic differences present between the family and the educational community (Khalfaoui et al, 2020; Río Ruiz, 2010), as well as financial difficulties that many of these families face (Clavell-Bate, 2012; Herrero et al, 2017; Marcu, 2020; Strataki and Petrogiannis, 2021), are additional barriers to interact with schools and, therefore, to support their children’s education.…”
Section: Introductionmentioning
confidence: 99%